Lęk przed matematyką przyszłych nauczycieli edukacji przedszkolnej i wczesnoszkolnej. Jak uczyć, kiedy sama się boję? - Monik Szczygieł; Krzysztof Cipora (Problemy Wczesnej Edukacji)
Maths anxiety is considered to be one of the important predictors of maths achievements. Numerous studies indicate that a teacher’s maths anxiety as well as teaching methods may be one of the causes of maths anxiety in children. Data obtained from American college students indicate that students choosing majors in pre-service education are characterised by very high levels of maths anxiety. In the presented paper we aimed at comparing maths anxiety in female students – future pre-service education teachers and female students in other faculties. Our study shows that future pre-service teachers are characterised by considerably higher maths anxiety. The results are discussed in the context of possible interventions targeted on future teachers that may eventually lead to an increase in children’s maths achievements.